Psychological phases and meaning of life in times of social isolation due the COVID-19 pandemic a reflection in the light of Viktor Frankl (Research, Society and Development, 2020)
Introduction: Social isolation is one of the preventive measures during pandemics to reduce the transmission of new viruses, but it can have serious psychological repercussions. In this perspective, this study aims to reflect on the psychological phases and the meaning of life, unveiled by Viktor Frankl from the experience in concentration camps, relating to the current moment of social isolation due to the COVID-19. Method: Reflective description, with a phenomenological-existential basis by Viktor Frankl and his book ¨Em Busca de Sentido¨, as well as related national and international literature. Results: As a reflection between Frankl's experience and the current reactions of people in social isolation, the three psychological phases to be discussed are: 1) the State of Shock: A Pandemic in a globalized world 2) Apathy, adaptation and the meaning of life in fields: Unveiling the meaning in dark times and 3) Third: After being released: What to expect or what to do Final considerations: This study allowed to verify that the psychological and behavioral reactions in a state of confinement, were similar between concentration camps and the current social isolation. Frankl's experience of finding meaning in life in times of suffering is an example of overcoming and surviving for people experiencing social isolation in times of pandemic.